PREVALENCE OF MARES’ GRANULOSA THECA CELL TUMOR (GTCT) IN INDONESIA - Amrozi Amrozi; Juli Melia; Luci Parwati; Ligaya I.T.A. Tumbelaka (Universitas Syiah Kuala, 2019)
This study was conducted to determine the prevalence rate of mares’ GTCT in Indonesia. Ultrasound examination of ovaries were performed on mares in Java and Madura Island of Indonesia. Thirteen mares had been affected by GTCT from 2913 number of examinations. The prevalence rate of GTCT during year 2006 and 2007 were 4.71% and 5.56%, respectively followed by a decrease in prevalence rate of GTCT during 2008-2014. The reproductive cycle in a mare with GTCT had returned to normal 6 months after ovariectomy.